Expanding the distribution of Tapanhuacanga campinorum (K.Krause) P.L.R.Moraes (Rubiaceae, Rubioideae) to central-western Brazil: the first record for the State of Mato Grosso, in the Parque Estadual do Cristalino - Martins Do Carmo, Joao Afonso (2024)
We report the occurrence of Tapanhuacanga campinorumin the Parque Estadual do Cristalino, in the State of Mato Grosso, CentralWest Brazil. This represents the first record of the genus in this State and the species in this region of the country, since T. campinorumwas known only from the Amazonian campinas vegetation in the States of Amazonas and Pará, in the northern region of Brazil. We further comment on the distribution, conservation, and taxonomic aspects of this species.